Some studies on two-layer electromagnetically coupled microstrip antenna with dielectric cover - Vasistha P.; Vishvakarma B.R. (My University, 2025)
Experimental investigations are carried out for two configurations, namely a driven hexagonal patch and an electromagnetically coupled microstrip antenna (EMCA), with different dielectric superstrates. Superstrate loading of the antenna is found to cause a considerable shift in the resonance frequency. The driven patch with superstrate behaves as an RL network. The maximum bandwidth of 6.21% is observed for the EMCA with a bakelite superstrate when the dielectric constant of the superstrate and the substrate of the antenna are equal. © 1999 Taylor and Francis Group, LLC.